Correlation between Cytomegalovirus (CMV) Breakthrough in High-risk Solid Organ Transplant Recipient and Valganciclovir Dose Modification. (4th October 2017) - Lemos-Ramirez, Juan; Abreu-Lanfranco, Odaliz; Busto, Ramon Del; Ramesh, Mayur; Williams, Jonathan; Bhargava, Pallavi; Ordaya, Eloy; Alangaden, George
Abstract: Background: CMV disease in solid organ transplant (SOT) recipients remains an independent risk factor that adversely affects morbidity, mortality, graft function and graft survival. For SOT recipients with CMV seropositive donor status (D+)/recipient negative (R-) or (D±/R+) universal prophylaxis with valganciclvoir (VGCV) is commonly used prevent CMV disease. However breakthrough and late-onset CMV disease remains a challenge. Methods: We performed a retrospective study of all SOT recipients at our center from January 2013 to December 2015. VGCV 900 mg daily was used as prophylaxis for a period of 12 months for lung transplants and 6 months for all other SOT. Primary endpoint was to identify a correlation between CMV breakthrough and VGCV dose modification due to leukopenia and renal function. Secondary endpoints was identification of independent risk factors for CMV breakthrough. Patients with late-onset CMV disease after discontinuation of VGCV were excluded. Results: Of the 723 SOT recipients during the study period we identified 364 patients: 143 high-risk patients (D+/R-) and 221 patients moderate risk (D±/R+). Breakthrough CMV disease occurred in 20 cases. Dose adjustment of VGCV prior to breakthrough was done in 17/20 (85%) of cases. Independent risk factors in patients with breakthrough CMV disease vs. no CMV disease were: (D+/R-) status 15 vs. 5 (P <0.001) and steroid use ( P = 0.02). No statistical differences were noted related to induction or maintenance anti-rejection regimens other than steroids or underlying comorbidities. Mean time to CMV breakthrough disease was 139 days ± 80 d). Rates of rejection was comparable in both groups. Conclusion: CMV breakthrough while on VGCV prophylaxis is uncommon in SOT recipients. Dose modification of VGCV preceded breakthrough disease in 85% of cases. CMV (D+/R-) mismatch and steroids use was associated with CMV disease. Careful and frequent monitoring of patients for CMV disease should be conducted whenever dose modification of VGCV is done. Disclosures: All authors: No reported disclosures.